A study of incidence of fibroid uterus, symptomatology, and therapeutic outcome of different procedures in patients with fibroid uterus - Rohin; T. Deepthisri; N. Chaitanya (MRIMS Journal of Health Sciences, 2025)
Background: Fibroids are benign, monoclonal tumors of smooth muscle cells of myometrium. Due to wide spectrum of clinical symptoms, they represent tremendous public health burden on women and economic costs to society. Strategies are needed to prevent its formation to limit growth and to treat nonsurgically. Objective: The objective of the study was to study the incidence of fibroid uterus, symptomatology, and therapeutic outcome of different procedures in fibroid uterus. Materials and Methods: Hospital-based prospective study was carried out among 14,250 patients. Among them, 3277 patients had fibroid uterus and 100 cases were included. Diagnosis was made by clinical examination and confirmed by radiological evaluation. Asymptomatic patients were monitored at every 6 months with pelvic examination and pelvic ultrasonography to determine growth rate of fibroid and symptoms. Medical therapy with gonadotropin-releasing hormone agonist was given as an adjunct to surgical treatment where temporary postponement of surgery was required. Myomectomy, laparoscopic myomectomy, hysteroscopic myoma resection, uterine artery embolization and hysterectomy were performed as per individual patient indication. Postoperatively, all patients were followed for 1 year, and outcome of various procedures in relieving symptoms and fertility was recorded. Results: The incidence of fibroid uterus was 23%. The incidence of fibroid was more in 31–35 years, in nulliparous women. The incidence of symptoms was 52%; most common was menorrhagia (44.2%). Dysmenorrhea was the most common cause of pain (37.5%). Proportion of patients got relieved of symptoms was the highest with hysterectomy (92%). Highest conception rate was after laparotomy/myomectomy in 58.3%. Conclusion: Dysmenorrhea was the most common cause of pain. Hysterectomy was best for relief of symptoms. Laparotomy/myomectomy was best for those who want to conceive.